The roles of cancer stem cells and therapeutic implications in melanoma - Mu, Xiaoli; Zhou, Yixin; Yu, Yongxin; Zhang, Mingyi (Frontiers in Immunology, 2024)
Melanoma is a highly malignant skin tumor characterized by high metastasis and poor prognosis. Recent studies have highlighted the pivotal role of melanoma stem cells (MSCs)—a subpopulation of cancer stem cells (CSCs)—in driving tumor growth, metastasis, therapeutic resistance, and recurrence. Similar to CSCs in other cancers, MSCs possess unique characteristics, including specific surface markers, dysregulated signaling pathways, and the ability to thrive within complex tumor microenvironment (TME). This review explored the current landscape of MSC research, discussing the identification of MSC-specific surface markers, the role of key signaling pathways such as Wnt/β-catenin, Notch, and Hedgehog (Hh), and how interactions within the TME, including hypoxia and immune cells, contribute to MSC-mediated drug resistance and metastatic behavior. Furthermore, we also investigated the latest therapeutic strategies targeting MSCs, such as small-molecule inhibitors, immune-based approaches, and novel vaccine developments, with an emphasis on their potential to overcome melanoma progression and improve clinical outcomes. This review aims to provide valuable insights into the complex roles of MSCs in melanoma biology and offers perspectives for future research and therapeutic advances against this challenging disease.